Fostering online relationships with brands through websites and social media brand pages - Pinto, L.; Loureiro, S. M. C.; Rita, P.; Sarmento, E. M. (Journal of Promotion Management, 2019)
The current study explores how brands create and maintain online relationships with consumers through their Websites, Facebook and Instagram brand pages. Findings show that Websites perform better in the two strategies disclosure and information dissemination. Regarding the strategy interactivity and involvement, websites lack interactive features that allow firms to engage with consumers, such as commenting and sharing opportunity. Managerial implications of the study are also provided.